TINJAUAN MASHLAHAH MURSALAH TENTANG TRADISI APHUBU DALAM WALIMATUL ‘URSY DI DESA SOBIH KECAMATAN BURNEH KABUPATEN BANGKALAN - FAIZ MUSHTOFA; MASROKHIN (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This thesis aims to find out the review of Islamic law related to the aphubu tradition in walimatul 'ursy that occurs in Sobih village, the understanding of the aphubu tradition according to the community, the social influence that occurs in the community of the aphubu tradition and how to review the mashlahah mursalah about the aphubu tradition in walimatul 'ursy. This research is a descriptive qualitative research using field studies or empirical using a sociological approach. The author used three data collection techniques, namely interviews, observations, and documentation. Meanwhile, in the analysis used are reduction techniques, presentation and drawing data conclusions. The conclusion of the research in general that, the tradition of aphubu in walimatul 'ursy in Sobih Village has occurred since a long time ago and has become a habit of the community when there is a walimah event almost all people continue to do aphubu, this activity is a problem because it concerns the economy because this aphubu must be returned in this case the review of mashlahah mursalah related to the aphubu tradition is Viewed in terms of the value of mashlahah with the mafsadah is greater than the value of the mashlahah, but in its implementation the community needs to know the aphubu that can be done according to the Mursalah mashlahah review so that things do not happen that cause the value of the mafsadah to be greater than the value of the mashlahah.